Risks of Commercialization of Intellectual Work Results: Appraisal Methods - A. V. Egiazaryan (Вестник Российского экономического университета имени Г. В. Плеханова)
The article studies different interpretations of the notion ‘risk’, which can help understand its nature and importance in the context of innovation. Special attention is paid to risks arising at different stages of innovation life cycle, such as idea, development, introduction and support. Reasons for these risks arising are investigated, which can be both internal, i. e. connected with the organization and project management and external, i. e. dealing with market situation and regulatory environment. The author studied methods of risk appraisal, including description of their step-by-step application, which can make the process more transparent and accessible for practical use. The obtained results were structured in the form of a table, where methods of risk appraisal are compared with stages of innovation commercialization and key drawbacks of each group of methods are identified. It makes the article valuable for experts on risk management, researches in the field of innovation and decision-makers wishing to manage risk efficiently at each stage of the innovation process as effective risk management is a key element in successful implementation of innovation projects and can minimize uncertainties connected with this dynamic field of activity.